2013
DOI: 10.1039/c2tb00223j
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional hybrid silica nanoparticles for controlled doxorubicin loading and release with thermal and pH dual response

Abstract: Controlled drug loading and release into tumor cells to increase the intracellular drug concentration is a major challenge for cancer therapy due to resistance and inefficient cellular uptake. Here a temperature and pH dually responsive PNiPAM/AA@SiO2 core-shell particles with internal controlled release were designed and fabricated for efficient cancer treatment, which could recognize the intrinsic pH differences between cancers and normal tissues. Upon lowering the temperature, doxorubicin was loaded into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
93
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(95 citation statements)
references
References 45 publications
0
93
0
2
Order By: Relevance
“…Among them, ordered mesoporous silicas of MCM-41 type are the most promising solid supports for the formation of biologically active systems (Aznar et al, 2011;Bernardos et al, 2010;Gu et al, 2012;Hu et al, 2013;Knezevic et al, 2011Knezevic et al, , 2013Lee et al, 2010Lee et al, , 2011Meng et al, 2010;Prokopowicz et al, 2016;Yuan et al, 2011). Besides chemical stability and biocompatibility, the potential importance of MCM-41 silica materials as drug carriers is caused by their high surface area, large pore volume, uniform and tunable pores of molecular size, and controllable participation in chemical reactions with a wide range of modifiers.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among them, ordered mesoporous silicas of MCM-41 type are the most promising solid supports for the formation of biologically active systems (Aznar et al, 2011;Bernardos et al, 2010;Gu et al, 2012;Hu et al, 2013;Knezevic et al, 2011Knezevic et al, , 2013Lee et al, 2010Lee et al, , 2011Meng et al, 2010;Prokopowicz et al, 2016;Yuan et al, 2011). Besides chemical stability and biocompatibility, the potential importance of MCM-41 silica materials as drug carriers is caused by their high surface area, large pore volume, uniform and tunable pores of molecular size, and controllable participation in chemical reactions with a wide range of modifiers.…”
Section: Introductionmentioning
confidence: 99%
“…In order to prevent undesirable release of Dox molecules at the first contact of carrier with aqueous solution and provide their liberation only in specific time and location, stimuli-responsive structures were constructed on MCM-41 surface. In particular, effective Dox release systems, which respond to the enzyme presence (Bernardos et al, 2010), light initiation (Knezevic et al, 2011), pH change (Bernardos et al, 2010;Gu et al, 2012;Hu et al, 2013;Knezevic et al, 2011;Lee et al, 2010Lee et al, , 2011Meng et al, 2010;Yuan et al, 2011), and temperature variation (Aznar et al, 2011;Hu et al, 2013), were reported. At the same time, because of the low loading efficiency of initial MCM-41 (up to 2.6 wt.%) (Kim et al, 2013), many attempts were made to enhance affinity between Dox molecules and silica surface by lining mesopore walls with functional groups (Kardys et al, 2013;Kim et al, 2013;Knezevic et al, 2011;Ma et al, 2014) or immobilization of polymer moieties on outer surface of silica particles (Kim et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hemolysis assay was done by method as described by Hu et al [13]. Two ml of heparinized blood was added to 4 ml sterile Dulbecco's phosphate buffer saline (DPBS) and centrifuged at 3000 rpm for 5 min using clinical centrifuge (REMI R-8C) to wash Red Blood Cells (RBCs).…”
Section: Hemolysis Assaymentioning
confidence: 99%
“…14,15 Taking these differences as a basic concept, various pH and temperature responsive polymers were synthesized and utilized as carriers for stimuli-responsive delivery of anti-cancer drugs. [16][17][18][19][20] Though all these reported polymeric nanoparticles have shown tremendous potential for targeted drug delivery, they have a very low drug loading capacity. Among them, due to the closer LCST (32 o C) of PNIPAAm to normal body temperature, biocompatibility and non-toxicity, chitosan-g-poly(N-isopropylacrylamide) (CS-g-PNIPAAm) co-polymer was most extensively studied as a carrier for anticancer drugs to achieve thermo and pH responsive delivery of drugs to the intended sites with minimal or no adverse effects in cancer therapy.…”
Section: Introductionmentioning
confidence: 99%